Effects of an extended version of the Lee Silverman Voice Treatment on voice and speech in Parkinson's disease. - Spielman J; Ramig LO; Mahler L; Halpern A; Gavin WJ (American Journal of Speech-Language Pathology, 2007)
PURPOSE: The present study examined vocal SPL, voice handicap, and speech characteristics in Parkinson's disease (PD) following an extended version of the Lee Silverman Voice Treatment (LSVT), to help determine whether current treatment dosages can be altered without compromising clinical outcomes. METHOD: Twelve participants with idiopathic PD received the extended treatment version (LSVT-X), similar to LSVT except that it was administered twice a week in 1-hr sessions over 8 weeks and required substantially more home practice. Recordings were made in a sound-treated booth immediately before and after treatment, and again 6 months later. Vocal SPL was measured for 4 different tasks and compared with data from a previous study, in which participants with PD received traditional LSVT 4 times a week for 4 weeks. Listener ratings were conducted with audio samples from both studies, using sentence pairs from a standard passage. LSVT-X participants completed the Voice Handicap Index (VHI) before each set of recordings. RESULTS: Participants receiving LSVT-X significantly increased vocal SPL by 8 dB after treatment and maintained increased vocal SPL by 7.2 dB at 6 months. VHI scores improved for 25% of the LSVT-X participants following treatment, and listener ratings indicated audible improvement in speech. CONCLUSIONS: LSVT-X successfully increased vocal SPL (which was consistent with improvements following traditional LSVT), decreased perceived voice handicap, and improved functional speech in individuals with PD. Further large-scale research is required to truly establish LSVT-X efficacy.